Emerging VEGF-receptor inhibitors for colorectal cancer. (March 2013) - Martinelli, Erika; Troiani, Teresa; Morgillo, Floriana; Orditura, Michele; De Vita, Fernando; Belli, Giulio; Ciardiello, Fortunato
<x xml:space="preserve">Abstract</x> Introduction: Targeted agents have dramatically improved and enriched the therapeutical choices for patients with metastatic colorectal cancer (mCRC). By better understanding the role of the angiogenic pathway in colorectal cancer (CRC), new therapies have been developed. Bevacizumab, the first anti-angiogenetic agent approved for the treatment of mCRC provide a proof of concept since it has improved the progression-free survival and overall survival when combined with cytotoxic chemotherapy. Areas covered: This review is focused on the most recent findings on the VEGF signaling pathway and new therapeutic drugs explored in clinical trials. Expert opinion: Despite the advantage offered by bevacizumab, the median overall survival of mCRC patient exceeds 21 months; thus, investigational efforts are needed. Several antiangiogenic agents for the treatment of mCRC are being tested in preclinical and clinical Phase I/II trials. Unfortunately a discrete number of Phase III trials produced negative results. Recently aflibercept and regorafenib, two new antiangiogenic drugs, have been approved as the new-targeted agents for the treatment of mCRC, according to the positive findings from the VELOUR and the CORRECT studies. In order to maximize clinical impact it will be important to validate predictive biomarkers and best combination treatments to offer for mCRC patients; further research and intense investigation is still required.